Sex-specific association between prenatal androgenization (second-to-fourth digit length ratio) and frontal brain volumes in adolescents - Lenz, Bernd; Gerhardt, Sarah; Boroumand-Jazi, Rafat; Eichler, Anna; Buchholz, Verena Nadine; Fasching, Peter Andreas; Kornhuber, Johannes; Banaschewski, Tobias; Flor, Herta; Guldner, Stella; Prignitz, Maren; Nees, Frauke (European archives of psychiatry and clinical neuroscience, 2023)
Prenatal androgenization associates sex-dependently with behavior and mental health in adolescence and adulthood, including risk-taking, emotionality, substance use, and depression. However, still little is known on how it affects underlying neural correlates, like frontal brain control regions. Thus, we tested whether prenatal androgen load is sex-dependently related to frontal cortex volumes in a sex-balanced adolescent sample. In a cross-sectional magnetic resonance imaging study, we examined 61 adolescents (28 males, 33 females; aged 14 or 16 years) and analyzed associations of frontal brain region volumes with the second-to-fourth digit length ratio (2D:4D), an established marker for prenatal androgenization, using voxel-based morphometry in a region-of-interest approach. Lower 2D:4D (indicative of higher prenatal androgen load) correlated significantly with smaller volumes of the right anterior cingulate cortex (r-ACC; β = 0.45) in male adolescents and with larger volumes of the left inferior frontal gyrus orbital part (l-IFGorb; β = - 0.38) in female adolescents. The regression slopes of 2D:4D on the r-ACC also differed significantly between males and females. The study provides novel evidence that prenatal androgenization may influence the development of the frontal brain in a sex- and frontal brain region-specific manner. These effects might contribute to the well-known sex differences in risk-taking, emotionality, substance use, and depression. Future research is needed to elucidate the role of prenatal androgenization within the biopsychosocial model.